Genomic Insights Into the Antifungal Activity and Plant Growth-Promoting Ability in Bacillus velezensis CMRP 4490 - Teixeira, Gustavo Manoel; Mosela, Mirela; Nicoletto, Maria Luiza Abreu; Ribeiro, Renan Augusto; Hungria, Mariangela; Youssef, Khamis; Higashi, Allan Yukio; Mian, Silas; Ferreira, André Sampaio; Gonçalves, Leandro Simões Azeredo; Pereira, Ulisses de Padua; de Oliveira, Admilton Gonçalves (Frontiers in Microbiology, 2021)
The main objective of this study was to evaluate the potential of B. velezensis strain CMRP 4490 as inhibition of soilborne plant pathogens and increased plant growth. The study included evaluation of in vitro antifungal control, sequencing the bacterial genome, mining genes responsible for the synthesis of secondary metabolites, root colonization ability, and greenhouse studies were carried out to plant growth promotion. The strain was obtained from soil samples in north of Paraná in Brazil and was classified as a B. velezensis, which consider a promising biological control agent. In vitro assay showed that B. velezensis CMRP 4490 presented antagonistic activity against Sclerotinia sclerotiorum, Macrophomina phaseolina, Botrytis cinerea and Rhizoctonia solani. To well understand this strain and to validate its effect as plant-growth promoting rhizobacteria, it was decided to explore its genetic content through genome sequencing, in vitro, and greenhouse studies. The genome of CMRP 4490 was estimated at 3,996,396 bp with a GC content of 46.4% and presents 4,042 coding DNA sequences. Biosynthetic gene clusters (BGCs) related to the synthesis of molecules with antifungal activity were found in the genome. Genes linked to the regulation/formation of biofilms, motility, and important properties for rhizospheric colonization were also found in the genome. Application of CMRP 4490 as a coating film on soybean and maize seeds improved germination and promoted radicular growth. The results indicated that B. velezensis CMRP 4490 could be a potential biocontrol agent and plant-growth promoting.